Transcatheter Device Closure of Muscular Ventricular Septal Defect - Yun-Ching Fu (Pediatrics and Neonatology)
Traditional treatment of muscular ventricular septal defect (VSD) is surgical closure, but it carries considerable morbidity and mortality. The Amplatzer muscular VSD occluder (AGA Medical Corporation, Plymouth, MN, USA) was approved by the United States Food and Drug Administration in September 2007 and by the Taiwan Department of Health in September 2009. It is a self-expandable double-disc device made from a nitinol wire mesh. Dacron polyester patches are sewn into each disc and the connecting waist to increase the thrombogenicity of the device. Many reports have shown that transcatheter device closure of muscular VSDs is effective and safe. It has no scar, less pain, shorter hospital stay, and less cost compared to the traditional open heart surgery.